(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The objective of present research work was to develop solid dispersion of Nystatin by using different concentrations of drug and polymer ratio. The effect of different concentrations of polymers was determined on the drug content and percentage cumulative drug release. Drug release followed zero-order models and mechanism of drug release are independent on the concentration of a drug.